Lexical composition in children with autism spectrum disorder (ASD)*. Issue 1 (5th December 2012) - RESCORLA, LESLIE; SAFYER, PAIGE
ABSTRACT: For sixty-seven children with ASD (age 1;6 to 5;11), mean Total Vocabulary score on the Language Development Survey (LDS) was 65·3 words; twenty-two children had no reported words; and twenty-one children had 1–49 words. When matched for vocabulary size, children with ASD and children in the LDS normative sample did not differ in semantic category or word-class scores. Q correlations were large when percentage use scores for the ASD sample were compared with those for samples of typically developing children as well as children with vocabularies <50 words. The 57 words with the highest percentage use scores for the ASD children were primarily nouns, represented a variety of semantic categories, and overlapped substantially with the words having highest percentage use scores in samples of typically developing children as well as children with lexicons of <50 words. Results indicated that the children with ASD were acquiring essentially the same words as typically developing children, suggesting delayed but not deviant lexical composition.